SECURITY ANALYSIS OF LIGHTWEIGHT CRYPTOGRAPHIC ALGORITHMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper examines three lightweight cryptographic algorithms - SKINNY, ForkAE, and Romulus. The research focuses on evaluating their security against various cryptographic attacks. Methods used: theoretical analysis and summary. Results indicate that all three algorithms exhibit strong security properties against common cryptographic attacks. SKINNY stands out for its security even with few encryption rounds, while the presence of SKINNY as a building block in the other two ciphers - ForkAE and Romulus makes them at least as secure as SKINNY.